2015
DOI: 10.1038/srep07856
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Environment Inhibits Mouse Pancreatic Cancer Growth and Down-regulates the Expression of Mitochondria-related Genes in Cancer Cells

Abstract: Psycho-social stress has been suggested to influence the development of cancer, but it remains poorly defined with regard to pancreatic cancer, a lethal malignancy with few effective treatment modalities. In this study, we sought to investigate the impacts of enriched environment (EE) housing, a rodent model of “eustress”, on the growth of mouse pancreatic cancer, and to explore the potential underlying mechanisms through gene expression profiling. The EE mice showed significantly reduced tumor weights in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 60 publications
3
56
0
Order By: Relevance
“…Our previous studies show that metabolic changes are associated with the tumor resistance found after living in an EE (16). In particular, tumor growth is linked with higher β-AR activity in white adipose tissue leading to reduce circulating leptin concentrations (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies show that metabolic changes are associated with the tumor resistance found after living in an EE (16). In particular, tumor growth is linked with higher β-AR activity in white adipose tissue leading to reduce circulating leptin concentrations (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an EE inhibits tumor progression in an implantation model of melanoma as well as a genetic model of colon cancer (14). Recent reports from others have shown the anticancer effects of an EE in orthotopic and spontaneous tumor models of breast, colon, pancreatic, and melanoma cancers (15, 16). We have identified one mechanism underlying the effects of an EE on metabolism and cancer, the activation of the hypothalamic-sympathoneural-adipocyte (HSA) axis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, enrichment delayed onset of the cancer through a reduction in leptin levels. Enrichment consisting of inanimate objects, social stimulation and exercise was found to inhibit pancreatic cancer growth in both subcutaneous and orthotopic models . (p3) The same impact on BDNF was observed as had been reported by other laboratories, and it was observed that enrichment induced differential expression (downregulated) of genes, mostly located in the mitochondria of the tumors.…”
Section: Effects Of Enrichmentmentioning
confidence: 99%
“…Reports from others confirm the anticancer effects of an EE in breast and pancreatic cancers [4,5]. Our previous studies have uncovered one underlying mechanism, the activation of a specific neuroendocrine axis: the Hypothalamic-Sympathoneural-Adipocyte (HSA) axis.…”
Section: Editorialmentioning
confidence: 73%